Innovation of INFIS (Integrated Natuna Financial Information System) and SALAM LABURA in Optimization of Public Services in Natuna and South Labuhanbatu District - Tukino Tukino (Inovbook Publications, 2022)
This research is about public service innovation through Electronic Government (e-government). This research is interesting and relevant to study considering that the two innovations created use technology in the process of their use. With the use of technology, of course, it will have a lot of positive impacts on society because it is considered more efficient. With this research, it is hoped that it can become a learning medium for other regions in making innovations to facilitate the community in realizing efficient public services. The population in this study is in areas that have implemented policies orinnovation in public services by utilizing technology. While the sample in this study isthe innovation of Salam Labura and the Smart Application for Integrated Licensing Services for the Public (SiCANTIK) which are innovations created by North Labuhanbatu Regency. The results of this study indicate that North Labuhanbatu Regency has succeeded in realizing optimal public services by implementing good e-government by creating various electronic-based innovations such as the Salam Labura innovation and the Smart Application for Integrated Licensing Services for the Public (SiCANTIK). Where, the Salam Labura innovation is a community report application system that is intended to facilitate the community in conveying their aspirations to the Regional Government of North Labuhanbatu Regency. While the use of SiCANTIK aims to facilitate the licensing service process.